Smooth and sharp-boundary inversion of two- dimensional pseudosection data in presence of a decrease in resistivity with depth (2002)
The smooth and sharp-boundary inversion of two-dimensional (2D) apparent resistivity pseudosection data in cases where the half-space has a lower resistivity than the overburden is investigated. The study entailed calculation (by forward modelling) of the synthetic data over simple 2D geologic models and inversion of the data. The 2D structures modelled include vertical fault, graben and horst. The Wenner array was used. The results show that there is generally an improvement in the model misfit with iteration number in smooth inversion; the algorithm can then be expected to iterate to the best solution at a high iteration number where the model resistivity of the substratum approaches the true bedrock resistivity. Inversion of the data using sharp boundaries indicates that the range of 2D equivalence, for which a reasonable interpretation could be attained, is relatively narrow. For the equivalent solutions, the data misfit between the observed and the calculated data is very small while model interpretations that are wrong can be readily identified on account of very large data misfits. A field example is given from Nauen, northern Germany, where partly-saturated sand of high resistivity is underlain in succession by less resistive saturated sand and glacial till; the smooth and sharp-boundary inversion results are in good agreement with the geo-radar and surface magnetic nuclear resonance (SNMR) and borehole information